RAPD-based genotyping of Malassezia pachydermatis from Domestic and wild animals - Kagueyama, Franciele Cristina; Moraes, Danny Franciele Dias; Rosa, Janaina Marcela Assunção; Ito, Alessandra Tammy Hayakawa; Silva, Aline de Jesus da; Batista, Gabriela Cardoso; Nakazato, Luciano; Dutra, Valéria (Semina: Ciências Agrárias, 2016)
Malassezia pachydermatis (M. pachydermatis) is a fungus of importance in human and veterinary medicine. Although a part of the normal microbiota, it can sometimes be present in its pathogenic form, particularly causing otitis and dermatitis in animals. Among human beings, it mainly affects immune compromised patients and newborns, causing simple pustulosis, seborrheic dermatitis, tinea versicolor or fungemia. This study aimed to analyze the genomic polymorphism in M. pachydermatis samples isolated from Canis familiaris (domestic dog), Felis catus (domestic cat), and Myrmecophaga tridactyla (giant anteater). Two hundred and fourteen samples were collected and cultured in Sabouraud agar with chloranphenicol (100mg L-1) and incubated at 37 Â°C for a period of 7 to 10 days. One hundred and sixty six samples that appeared morphologically comparable to yeast cultures were processed for DNA extraction and PCR was performed for a specific region in the Internal Transcribed Spacer (ITS) of M. pachydermatis. Among these, seven (4.21%) were negative and 159 (95.79%) were positive. Of the 159 positive samples, 102 (64.15%) were from animals with clinical signs and 57 (35.85%) without clinical signs. Fifty-seven samples were selected at random for RAPD-PCR based genotyping and distributed into four genetic groups. Types I and II were more frequent in animals with clinical signs while type III was frequent in healthy animals. Type IV occurred evenly across animals with or without clinical signs. These results indicate differences in pathogenicity of the fungus based on the genotype.